PENGARUH KUALITAS LAYANAN DAN KEPERCAYAAN TERHADAP MINAT PENGGUNA: (Studi Kasus Pada Pengguna Fitur Shopee Paylater) - Nanda Ayu (ECONOMOS, 2022)
Shopee is an electronic trading center headquartered in Singapore under the auspices of SEA Group (formerly known as Garena). Shopee was founded in 2009 by Forrest Li. Shopee first launched in Singapore in 2015 . Shopee pay later is a loan product in collaboration with other Fintech Lending. Shopee as an e-commerce platform provides services to Fintech Lending to fund users who need financial assistance in the form of balances to chat in shopee. This type of research is quantitative research, in this study uses quantitative analysis techniques that are data collection techniques in the form of numbers obtained from questionnaire results and then the data is processed and analyzed using statistics. Through the results of statistical tests, it can be concluded that the Service Quality and Trust variables have a positive and significant influence on user interests of Shopee pay later features. Partially independent variable X1 i.e. Quality of Service has a positive and significant influence on the depenen variable that is user interest. This can be seen from the value of t calculated which is 10,936 greater than the tablet which is 1,988 which means the quality of service has a considerable influence on the interest of users of shopee pay later features. In partial independent variable X2 i.e. Trust has a positive and significant influence on the dependent variable that is User Interest. This can be seen from the value of t calculated 5,267 greater than the tablet which is 1.988 which means trust has a considerable influence on the interest of users of the Shopeee pay later feature.